Solution conformation of a parallel DNA triple helix with 5' and 3' triplex-duplex junctions. - Asensio, J; Brown, T; Lane, A (1999)
BACKGROUND: Polypurine x polypyrimidine sequences of DNA can form parallel triple helices via Hoogsteen hydrogen bonds with a third DNA strand that is complementary to the purine strand. The triplex prevents transcription and could therefore potentially be used to regulate specific genes. The determination of the structures of triplex-duplex junctions can help us to understand the structural basis of specificity, and aid in the design of optimal antigene oligonucleotides. RESULTS: The solution structures of the junction triplexes d(GAGAGACGTA)-X-(TACGTCTCTC)-X-(CTCTCT) and d(CTCTCT)-X-(TCTCTCAGTC)-X-(GACTGAGAGA) (where X is bis(octylphosphate) and nucleotides in the triplex regions are underlined) have been solved using nuclear magnetic resonance (NMR) spectroscopy. The structure is characterised by significant changes in the conformation of the purine residues, asymmetry of the 5' and 3' junctions, and variations in groove widths associated with the positive charge of the protonated cytosine residues in the third strand. The thermodynamic stability of triplexes with either a 5' or a 3'CH+ is higher than those with a terminal thymidine. CONCLUSIONS: The observed sequence dependence of the triplex structure, and the distortions of the DNA at the 5' and 3' termini has implications for the design of optimal triplex-forming sequences, both in terms of the terminal bases and the importance of including positive charges in the third strand. Thus, triplex-stabilising ligands might be designed that can discriminate between TA x T-rich and CG x C+-rich sequences that depend not only on charge, but also on local groove widths. This could improve the stabilisation and specificity of antigene triplex formation.